2017
DOI: 10.1002/ejoc.201601568
|View full text |Cite
|
Sign up to set email alerts
|

Thio‐ and Seleno‐Dioxaphosphorinane‐Constrained Dinucleotides (D‐CNA): Synthesis and Conformational Study

Abstract: Thio‐ and seleno‐α,β‐ and α,β,γ‐D‐CNA (constrained nucleic acid) dinucleotides in which two or three torsion angles of the sugar/phosphate backbone are controlled within a dioxaphosphorinane structure have been prepared. Their structural determination was carried out by means of NMR spectroscopy to show only slight variation on the torsion‐angle control in comparison with their oxo analogues. Unexpected selenium migration has been pointed out from selenophosphotriester moiety to phosphoramidite group, but this… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 37 publications
0
4
0
Order By: Relevance
“…In silico -C2NA structure conformational study As previously observed with -CNAs, 9,12,14 among the four possible -C2NAs isomers, only two of them can have all the substituents of the phosphorinane ring in the orientation that favours their formation, stability and conformational interest: the upper nucleoside in the apical position, the exocyclic oxygen and the lower nucleoside in equatorial position. Moreover in line with the results obtained with their -CNA analogues, a simple molecular model examination indicated that this couple should mainly differ on the  torsional angle conformation.…”
Section: Resultsmentioning
confidence: 81%
See 1 more Smart Citation
“…In silico -C2NA structure conformational study As previously observed with -CNAs, 9,12,14 among the four possible -C2NAs isomers, only two of them can have all the substituents of the phosphorinane ring in the orientation that favours their formation, stability and conformational interest: the upper nucleoside in the apical position, the exocyclic oxygen and the lower nucleoside in equatorial position. Moreover in line with the results obtained with their -CNA analogues, a simple molecular model examination indicated that this couple should mainly differ on the  torsional angle conformation.…”
Section: Resultsmentioning
confidence: 81%
“…They are both obtained in moderate to good yield by displacement by the propargylamine of a tosylate group of tosyloxyethyl thymidines 1 and 9, respectively, both previously described in the preparation ofD-CNAs. 14 Thanks to the methodology elaborated by A. Kraszewski and collaborators in the early 90's, preactivation of the thymidine Hphosphonate monoester by pivaloyl chloride led to a dipivaloyl phosphite that can react with the amino alcohol derivative to form a cyclic phosphoramidite intermediate, further oxidized in situ by water after addition of iodine that provided the oxaza-phosphorinane. 15 This procedure led in average yield of 80% from 5'-C(S)-propargylaminoethyl thymidine 2 to a 2:1 ratio of diastereoisomeric oxaza-phosphorinane dinucleotides -C2NAs 3 and 4, determined by 31 P NMR (= 2.4 and 4.7 ppm for 3 and 4, respectively, Scheme 1).…”
Section: Synthesis Of -C2namentioning
confidence: 99%
“…This approach has allowed us to prepare all the possible α,β- D -CNA diastereoisomers [ 123 ]. Finally, the family was completed by the thio- and seleno-α,β- D -CNA diastereoisomers that displayed the same torsional angles values as their oxo-counterparts [ 124 ].…”
Section: Structuration Of Nucleic Acids (Cna)mentioning
confidence: 99%
“…Restricting the torsion angles of the phosphate backbone in oligonucleotides can also improve their duplex-forming ability. Bicyclo-DNAs and tricyclo-DNAs, which are nucleic acid derivatives with a constrained torsion angle γ, can form thermally stable duplexes with complementary RNA. Moreover, constrained nucleic acid (CNA) derivatives have also been developed, in which the conformation of the phosphate backbone is fixed by a six-membered chair-form ring. Based on these strategies, restriction of both the sugar conformation and phosphate backbone is considered an effective approach for enhancing RNA-binding ability. In fact, tricyclic-LNA derivatives, which have a constrained N-type sugar and torsion angle γ, show excellent RNA-binding ability …”
Section: Introductionmentioning
confidence: 99%